Different Patterns of Spontaneous Brain Activity between Tremor‐Dominant and Postural Instability/Gait Difficulty Subtypes of Parkinson's Disease: A Resting‐State fMRI Study - Chen, Hui‐Min (CNS Neurosci Ther, 2015)
AIMS: Postural instability/gait difficulty (PIGD) and tremor‐dominant (TD) subtypes of Parkinson's disease (PD) show different clinical manifestations; however, their underlying neural substrates remain incompletely understood. This study aimed at investigating the subtype‐specific patterns of spontaneous brain activity in PD. METHODS: Thirty‐one patients with PD (12 TD/19 PIGD) and 22 healthy gender‐ and age‐matched controls were recruited. Resting‐state functional magnetic resonance imaging data were collected, and amplitude of low‐frequency fluctuations (ALFF) was measured. Voxelwise one‐way analysis of covariance and post hoc analyses of ALFF were performed among the three groups, with age and gender as covariates (levodopa daily dosage and gray matter volume as additional covariates for validation analysis). Correlations of clinical variables (e.g., disease duration and PIGD/tremor subscale score) with ALFF values were examined. RESULTS: Compared with controls, patients with TD exhibited higher ALFF in the right cerebellar posterior lobe and patients with PIGD exhibited lower ALFF in the bilateral putamen and cerebellar posterior lobe, and higher values primarily in several cortical areas including the inferior and superior temporal gyrus, superior frontal, and parietal gyrus. Compared with patients with PIGD, patients with TD had higher ALFF in the bilateral putamen and the cerebellar posterior lobe, as well as lower ALFF in the bilateral temporal gyrus and the left superior parietal lobule. In all patients, ALFF in the bilateral cerebellar posterior lobe positively correlated with tremor score and ALFF in the bilateral putamen negatively correlated with PIGD score. CONCLUSION: Different patterns of spontaneous neural activity in the cerebellum and putamen may underlie the neural substrate of PD motor subtypes.